2018
DOI: 10.1097/coc.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Acute and Chronic Wound Complications in Patients With Soft Tissue Sarcoma With Long-term Follow-up

Abstract: Several factors associated with acute and chronic wound complications were identified in STS patients including timing of RT, tumor site, and reconstruction use. The development of acute wound complications may also be associated with an increased risk of chronic wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
4
16
1
Order By: Relevance
“…The MWC-rate in our study (26.2% in the whole cohort; 35.9% in lower extremities) was in line with the data from other studies that investigated postoperative complications after multimodal treatment for STS (both neoadjuvant and adjuvant radiotherapy, partly complemented by other modalities) [5,15,[18][19][20][21]. Retroperitoneal STS were not included in most of the studies [13,15,18,20,21,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The MWC-rate in our study (26.2% in the whole cohort; 35.9% in lower extremities) was in line with the data from other studies that investigated postoperative complications after multimodal treatment for STS (both neoadjuvant and adjuvant radiotherapy, partly complemented by other modalities) [5,15,[18][19][20][21]. Retroperitoneal STS were not included in most of the studies [13,15,18,20,21,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, differences in inclusion of postoperative seroma treated with drainage or aspiration have been detected. Higher MWC-rates in patients treated with neoadjuvant therapy (23.8%-39.7%) compared to patients treated with adjuvant therapy (8.0-23.1%) were observed in various studies [5,13,15,[18][19][20][21]. However, no statistically signi cant difference between patients treated with neoadjuvant and adjuvant therapy was observed in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…to that reported in the literature for standard fractionation radiotherapy. 16 On the NCIC study reported by O'Sullivan et al, acute wound complications were recorded in 35% of patients who received preoperative radiotherapy vs 17% in those that received postoperative radiotherapy. 17 Of the patients who underwent preoperative radiotherapy, 16% of patients required reoperation due to treatment complications.…”
Section: Discussionmentioning
confidence: 97%
“…Wounds are classified on the basis of the various factors such as location, borders, size, tissue type, secretion, odor, edema, and pain ( Frykberg and Banks, 2015 ; Wernick and Stawicki, 2018 ). Based on these characteristics, they can be simple or complex, deep or superficial, acute or chronic, sterile or contaminated, or even defined by the type of healing ( Morton and Phillips, 2016 ; Karthik et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of chronic wounds is complex and can include the administration of vascular endothelial growth factor or erythropoietin, which may not always be efficient and present high costs and has short half-life and side effects ( Hong and Park, 2014 ; Arslantas et al, 2015 ; Yu et al, 2018 ). Moreover, the treatment of chronic wounds often requires the use of antimicrobials due to their multifactorial nature ( Karthik et al, 2018 ). Considering this aspect, the development of new therapies for wound healing requires immediate attention.…”
Section: Introductionmentioning
confidence: 99%